BUDAYA LOKAL YANG TERCERMIN DALAM METAFORA WACANA PASANG MASYARAKAT ADAT AMMATOA KAJANG KABUPATEN BULUKUMBA PROVINSI SULAWESI SELATAN - , Andi Karmila Ningsih ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pasang is an oral tradition which becomes a life guidance of the traditional society of Ammatoa Kajang. If it is being violated, it will cause unwanted things. The objectives of this research are to describe the linguistic units which are used as the revealed of the metaphors in the discourse of pasang